2020
DOI: 10.3390/ani10122320
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Cardiac Functions Using Full Conventional Echocardiography with Tissue Doppler Imaging before and after Xylazine Sedation in Male Shiba Goats

Abstract: The present study aimed to provide a complete conventional echocardiographic protocol in adult male Shiba goats by using two-dimensional, M-mode, Pulsed Wave Doppler, and tissue Doppler imaging (TDI) echocardiography, and to study concomitantly xylazine-induced alteration of cardiac functions in a highly sensitive species. For this purpose, 12 male Shiba goats were included and complete conventional echocardiography from the standard right and left parasternal views was carried to report the echocardiographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Besides, the echocardiography has been evaluated only from the right side and without Doppler evaluation of the ow tracts because of the di culty to obtain Doppler alignment in the standing position. This has been previously attributed to the presence of gases-lled rumen (Leroux et al 2012) in addition to the large-sized goats included in this study compared with goats used in our previous report (Mandour et al 2020b).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Besides, the echocardiography has been evaluated only from the right side and without Doppler evaluation of the ow tracts because of the di culty to obtain Doppler alignment in the standing position. This has been previously attributed to the presence of gases-lled rumen (Leroux et al 2012) in addition to the large-sized goats included in this study compared with goats used in our previous report (Mandour et al 2020b).…”
Section: Discussionsupporting
confidence: 49%
“…The ECG-derived data included wave durations measured as milliseconds (ms), voltage expressed as millivolt (mv), as well as cardiac intervals (PR, RR, ST, QT) derived from the standard ECG waves (P, QRS, and T) measured as ms (Koether et al 2016). In standing position, right side two-dimensional and short-axis M-mode echocardiography at the level of the papillary muscles were performed using the ultrasound machine (EUB-7500, Hitachi Medical Corporation, Tokyo, Japan) equipped with a sector probe (3-7 MHz; Model EUP-L65; Hitachi Medical Corporation, Tokyo, Japan) (Mandour et al 2020b). A detailed description of the preparation and recording procedures was previously described (Mandour et al 2021).…”
Section: Assessment Of Cardiac Functionsmentioning
confidence: 99%
“…Furthermore, it was assumed that CO is likely to be maintained or minimally increased after alfaxalone administration due to a transient increase in HR and increased venous return along with reduced venous compliance [ 33 , 34 ]. A recent study revealed a significant decrease in HR, FS and CO post xylazine sedation [ 40 ]. In this study, the echocardiographic parameters did not show any significant change in the XYL-ALF group, indicating that premedication with xylazine before alfaxalone induction has less impact on the cardiovascular system than ALF induction alone.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular diseases (CVDs) are accounted as one reason for death in the globe; the statistics of people who die due to CVDs are increasing every year [ 363 ]. The advancement of cardiac function assessment techniques enables early detection, even prediction of many CVDs [ [364] , [365] , [366] , [367] ]. Different tissue engineering strategies are employed to overcome this problem considering the limited potency of human cardiac cells to complete regeneration.…”
Section: Smart/stimuli-responsive Hydrogels Employed For Different Biomedical Applicationsmentioning
confidence: 99%